Um estudo e uma ferramenta de gerência de projetos com desenvolvimento ágil de software - Leonardo Aparecido Ciscon (2009)
The agile practices are being increasingly used in the management of software projects. This work studies the agile and traditional practices used in project management. In this study it was analyzed several organization aspects, in particular the characteristics of people and project practices. It is presented and discussed the participation of the project manager with emphasis in agile practices. As a complement of the work it was developed a tool called XPlannerPlus. XPlannerPlus was developed based on an existing web-based tool known as XPlanner. Another complement of this work is a case study conducted in a small software development organization. XPlannerPlus was used and the case study helped us to verify some of the aspects of our study as well as to test the tool itself.